Can Commercially Available Handheld Retinal Cameras Effectively Screen Diabetic Retinopathy?. (January 2017) - Cuadros, Jorge; Bresnick, George
Organizations that care for people with diabetes have increasingly adopted telemedicine-based diabetic retinopathy screening (TMDRS) as a way to increase adherence to recommended retinal exams. Recently, handheld retinal cameras have emerged as a low-cost, lightweight alternative to traditional bulky tabletop retinal cameras. Few published clinical trials have been performed on handheld retinal cameras. Peer-reviewed articles about commercially available handheld retinal cameras have concluded that they are a usable alternative for TMDRS, however, the clinical results presented in these articles do not meet criteria published by the United Kingdom Diabetic Eye Screening Programme and the American Academy of Ophthalmology. The future will likely remedy the shortcomings of currently available handheld retinal cameras, and will create more opportunities for preventing diabetic blindness.